Strategi peningkatan usaha pemasaran ikan hasil budidaya keramba jaring apung masyarakat Desa Kampung Panjang - Hayatul Ismi; Hasby Abiyyu Farras; Tanaya Annisa Putri; Ainul Mardiah; Theresia Evelina; Ranti Oktaviana; Roulina Matanari; Helfi Safrita; Allya Eka Nursanty; Yoga Saputra; Samuel Pakpahan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This research focuses on strategies to increase the marketing efforts of fish from the cultivation of floating net cages through the use of social media